2016
DOI: 10.1039/c6ra15891a
|View full text |Cite
|
Sign up to set email alerts
|

Sr- and Ni-doping in ZnO nanorods synthesized by a simple wet chemical method as excellent materials for CO and CO2 gas sensing

Abstract: In this study, the effect of Sr-and Ni-doping on microstructural, morphological and sensing properties of ZnO nanorods has been investigated. Nanorods with different Sr and Ni loadings were prepared using a simple wet chemical method and characterized by means of scanning electron microscopy (SEM), X-ray diffraction (XRD) and photoluminescence (PL) analysis. XRD data confirmed that Sr-and Ni-doped samples maintainsthe wurtzite hexagonal structure of pure ZnO. However, unlikes Sr, Ni doping modifies the nanorod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Although the change in the morphology of the nanostructured ZnO with increasing Mn 2+ concentration, observed by TEM and FTIR, is not a new phenomenon, a recently published review 38 regarding the inuence of ionic impurities on the phase and growth/morphology of semiconductor nanocrystals shows that, despite intensive research, there are fundamental issues still unsolved. Previous articles have reported morphological changes of the ZnO nanomaterials associated with the doping process, [39][40][41][42][43] which could be connected to specic structural and coordination properties, as further explained. The crystallographic plane with the minimum surface free energy determines the preferential growth direction.…”
Section: Ftir Measurementsmentioning
confidence: 72%
“…Although the change in the morphology of the nanostructured ZnO with increasing Mn 2+ concentration, observed by TEM and FTIR, is not a new phenomenon, a recently published review 38 regarding the inuence of ionic impurities on the phase and growth/morphology of semiconductor nanocrystals shows that, despite intensive research, there are fundamental issues still unsolved. Previous articles have reported morphological changes of the ZnO nanomaterials associated with the doping process, [39][40][41][42][43] which could be connected to specic structural and coordination properties, as further explained. The crystallographic plane with the minimum surface free energy determines the preferential growth direction.…”
Section: Ftir Measurementsmentioning
confidence: 72%
“…. The shifting of peak towards higher diffraction angle side is the evidence of lattice contractions 19 . This is due to the smaller cationic radius Li 1+ (0.167 nm) in comparison to V 5+ (0.171 nm).…”
Section: Resultsmentioning
confidence: 95%
“…This is due to the smaller cationic radius Li 1+ (0.167 nm) in comparison to V 5+ (0.171 nm). As a result of the substitution of the larger cationic radius of V by the smaller cationic radius of Li, the lattice compression (compressive strain) arises in the Li 0.04 V 2 O 5 crystalline phase 19 . Further comparing the peak intensities of the phases, it is observed that the intensity of the major phase Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…It clari es that there is no signi cant shift in the peak location. So, doping could not be happened [29]. No amorphous phase can be seen in DS9.…”
Section: The Effect Of Coating On the Nir Re Ectance Of The Powder Pimentioning
confidence: 97%